Prognostic significance of delirium in patients with heart failure: a systematic review and meta-analysis - Niu, Ziru; Zhou, Jiamin; Li, Yongjun (Frontiers in Cardiovascular Medicine, 2023)
Background Delirium is a common symptom of heart failure (HF) and is associated with increased mortality, prolonged hospital stays, and heightened medical costs. The impact of delirium on the prognosis of HF patients is currently controversial. Therefore, we conducted a meta-analysis to evaluate the prognostic significance of delirium in HF. Methods Relevant articles were systematically searched in PubMed, Cochrane Library, Web of Science, and Embase based on the PRISMA guidelines. Studies that reported mortality and hospitalization-related outcomes in HF patients with or without delirium using raw or adjusted hazard ratio (HR) and odds ratio (OD) were included. Meta-analysis was then performed to evaluate the effect of delirium in HF patients. Outcomes of interest were all-cause mortality and events of the hospitalization. Results Of the 1,501 studies identified, 7 eligible studies involving 12,830,390 HF patients (6,322,846 males and 6,507,544 females) were included in the meta-analysis. There were 91,640 patients with delirium (0.71%) and 12,738,750 patients without delirium (99.28%). HF patients with delirium had higher OR for in-hospital mortality (1.95, 95% CI = 1.30–2.91, P = 0.135), higher pooled HR for 90-day mortality (2.64, 95% CI = 1.06–1.56, P = 0.215), higher pooled HR for 1-year mortality (2.08, 95% CI = 1.34–3.22, P = 0.004), and higher pooled HR for 30-day readmission rate (4.15, 95% CI = 2.85–6.04, P = 0.831) than those without delirium. Conclusion Current evidence suggests that combined delirium increases the risk of HF-related mortality and hospitalization-related outcomes in patients with HF. However, more research is needed to assess the impact of delirium on the prognosis of HF patients.